(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2025)
This article summarizes thoughts about the necessity of education today and its main purpose. Also, the authority of education and its important aspects were deeply analyzed.